Разделяющее преобразование в экстремальных задачах о неналегающих областях и для открытых множеств - Вьюн, В.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The article is dedicated to the solution of new extremal problems on non-overlapping domains with free poles on a circle and to the extension of some famous results to the case of special classes of open sets.